Marine particle size distribution data obtained with an Underwater Vision Profiler 6 mounted on BGC Argo float WMO6903096 - Rainer Kiko; Lars Stemmann; Sabrina Speich; Birgit Klein; Edouard Leymarie; Antoine Poiteau; Herv Claustre; Camille Catallano; Marc Picheral (PANGAEA, 2023)
Here we provide particle size and biovolume distribution data from an Underwater Vision Profiler 6, mounted on a BGC Argo Float with the WMO number 6903096. The float was deployed in off Angola on the 5th May 2021 at 10.99 degree South, 12.73 degree East. Parking depth was alternated between 250, 500 and 1000 m m and profiling depth alternated between 1000 and 2000 m depth, whenever possible. Profiling frequency was every three days. The float was deliberately picked up on the 26 April 2023 at 11.14 degrees South and 11.22 degrees East.